A parametric sizing model for Molten Regolith Electrolysis reactors to produce oxygen on the Moon. Issue 7 (1st April 2016) - Schreiner, Samuel S.; Sibille, Laurent; Dominguez, Jesus A.; Hoffman, Jeffrey A.
Abstract: We present a parametric sizing model for a Molten Regolith Electrolysis (MRE) reactor that produces oxygen and molten metals from lunar regolith. The model has a foundation of regolith material property models validated using data from Apollo samples and simulants. A multiphysics simulation of an MRE reactor is developed and leveraged to generate a database linking reactor design and performance trends. A novel design methodology is created which utilizes this database to parametrically design an MRE reactor that can (1) sustain the required current, operating temperature, and mass of molten regolith to meet a desired oxygen production level, (2) operate for long periods of time by protecting the reactor walls from the corrosive molten regolith with a layer of solid "frozen" regolith, and (3) support a range of electrode separations to enable operational flexibility. Mass, power, and performance estimates for an MRE reactor are presented for a range of oxygen production levels. Sensitivity analyses are presented for several design variables, including operating temperature, regolith feedstock composition, and the degree of operational flexibility.